Analysis Of Quality Management And Product Design Problems Of PT L’essential Towards Customer Satisfaction - Alfonsus Nandi Kurniawan; Brigitta Denise Alexandra; Cindy Ariesta; Feony Valencia Yafinto; Riona Tamara; Hesti Maheswari (Citakonsultindo, 2025)
This research aims to analyze the quality management and product design issues faced by PT L’Essential and their impact on customer satisfaction. The main problems identified include a high rate of product defects, particularly in packaging such as leaking bottles and pump malfunctions, as well as a mismatch between packaging design and consumer expectations. To address these issues, a qualitative approach was employed through direct observation, semi-structured interviews, and the use of company data to support theoretical analysis. Analytical tools used include production process flowcharts, cause-and-effect diagrams, Pareto charts, and design-focused methods such as Quality Function Deployment (QFD) and Fault Tree Analysis (FTA) to identify root causes of design failures. The findings reveal that 70% of total product defects stem from two major types of failures: leaking bottles and pump malfunctions, which directly affect stock accuracy and distribution flow. The production yield rate was recorded at 93.63% with a productivity level of 5.85 units per hour, while the quality productivity ratio was only 23.25%, indicating untapped efficiency potential. The managerial implications of these findings highlight the need to strengthen quality control at the early stages of production, redesign packaging based on customer needs, and provide ongoing employee training. These strategies are expected to reduce defect rates, enhance operational efficiency, and strengthen customer loyalty toward PT L'Essential brand in the competitive skincare market.